2020
DOI: 10.1002/cbic.202000432
|View full text |Cite
|
Sign up to set email alerts
|

Triplex‐Forming Peptide Nucleic Acids with Extended Backbones

Abstract: Peptide nucleic acid (PNA) forms a triple helix with doublestranded RNA (dsRNA) stabilized by a hydrogen-bonding zipper formed by PNA's backbone amides (NÀ H) interacting with RNA phosphate oxygens. This hydrogen-bonding pattern is enabled by the matching~5.7 Å spacing (typical for A-form dsRNA) between PNA's backbone amides and RNA phosphate oxygens. We hypothesized that extending the PNA's backbone by one À CH 2 À group might bring the distance between PNA amide groups closer to 7 Å, which is favourable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We synthesized six PNAs having modified nucleobases with various fluorine substitution patterns (PNAX, Figure 2) ranging from none (X=F0) to fully substituted pentafluorobeznene (X=F5). PNA monomers were synthesized using our previously reported methods starting from commercially available substituted phenylacetic acids (for details, see Supporting Information) [9–10,19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized six PNAs having modified nucleobases with various fluorine substitution patterns (PNAX, Figure 2) ranging from none (X=F0) to fully substituted pentafluorobeznene (X=F5). PNA monomers were synthesized using our previously reported methods starting from commercially available substituted phenylacetic acids (for details, see Supporting Information) [9–10,19] …”
Section: Resultsmentioning
confidence: 99%
“…PNA monomers were synthesized using our previously reported methods starting from commercially available substituted phenylacetic acids (for details, see Supporting Information). [9][10]19] We evaluated the stability and specificity of base triplets involving fluorinated benzenes using UV thermal melting of the triple helices formed between model hairpins and modified PNAs. UV thermal melting is a common technique to measure stability of nucleic acid secondary structures; however, for triple helices the measurements may be complicated by overlap between the triplex to duplex and duplex to single strands transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, backbone modification has been a major focus of follow up attempts to improve the original PNA design. Early studies showed that maintaining proper distances (number of bonds) along the backbone and be-tween the backbone and nucleobases of PNA was critical for effective nucleic acid binding as extension of either by additional methylene groups strongly decreased the binding affinity of PNA to either single-or double-stranded nucleic acids [46][47][48]. Furthermore, replacing amide linkages connecting the PNA's backbone and the nucleobase with a tertiary amine also destabilized PNA complexes with complementary DNA [49].…”
Section: Pna Backbone Modificationsmentioning
confidence: 99%
“…Binding data suggest that increasing the length of the backbone or the backbone‐base linker significantly weakens the binding of PNAs to dsRNAs, ssRNAs, and dsDNAs. [ 64,71 ] NMR and fluorescence studies suggest that attaching a γ‐(R)‐hydroxymethyl group to PNAs containing bases T, M, and E results in a reduced PNA•dsRNA triplex formation and an enhanced invasion of a dsRNA to form a PNA•RNA‐PNA triplex. [ 55,72 ] Clearly, base modifications (Figures 3–7) combined with backbone/linker modifications (Figure 1) would allow the development of optimized PNA‐based scaffolds for the specific recognition of dsRNAs.…”
Section: Sequence‐specific Recognition Of Dsrnasmentioning
confidence: 99%